yggS Encoding Pyridoxal 5′-Phosphate Binding Protein Is Required for Acidovorax citrulli Virulence - Wang, Yuanjie; Zhao, Yuqiang; Xia, Liming; Chen, Lin; Liao, Yajie; Chen, Baohui; Liu, Yiyang; Gong, Weirong; Tian, Yanli; Hu, Baishi (Frontiers in Microbiology, 2022)
Bacterial fruit blotch, caused by seed-borne pathogen Acidovorax citrulli, poses a serious threat to the production of cucurbits globally. Although the disease can cause substantial economic losses, limited information is available about the molecular mechanisms of virulence. In this study, a random transposon insertion mutant impaired in the ability to elicit a hypersensitive response on tobacco was identified. The disrupted gene in this mutant was determined to be Aave_0638, that is predicted to encode a YggS family pyridoxal phosphate-dependent enzyme. YggS is a highly conserved protein among multiple organisms, and is responsible for maintaining the homeostasis of pyridoxal 5’-phosphate and amino acids in cells. A yggS deletion mutant of A. citrulli strain XjL12 displayed attenuated virulence, delayed hypersensitive response, less tolerance to H2O2 and pyridoxine, increased sensitivity to antibiotic β-chloro-D-alanine, reduced swimming while enhanced twitching motility. In addition, RNA-Seq analysis demonstrated that yggS was involved in regulating the expression of certain pathogenicity-associated genes related to secretion, motility, quorum sensing and oxidative stress response. Importantly, YggS significantly affected type III secretion system and its effectors. Collectively, our results suggest that YggS is indispensable for A.citrulli virulence, and expands the role of YggS in biological processes.